Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm reading Algebra 2e by Michael Artin. I'd be grateful for any guidance on 2 closely-related questions from Section 2.2, Groups and Subgroups, p. 42, excerpted below. First, I can understand the purpose and effect of the three rules listed, but I don't understand where they came from. Second, and similarly, I can see how the six elements of $S_{3}$ are non-overlapping and distinct, but I don't understand how they were derived. Where does the cancellation law fit in? (I'm going to press my luck and also ask how $x^{-1}$ in the first equation at the bottom is equal to $x^2$ in the second, by applying the first two rules). I am hoping these are simple and closely-enough related to hang together. If not, I would be glad to remove this and repost over a longer period. Cheers! Text:

To describe [$S_{3}$], we pick two particular permutations in terms of which we can write all others. We take the cyclic permutations ($\mathbf{1\ 2\ 3}$), and the transposition ($\mathbf{1\ 2}$), and label them as $x$ and $y$, respectively. The rules $x^3 = 1,\ y^2 = 1,\ yx = x^2y$ are easy to verify. Using the cancellation law, one sees that the six elements $1,\ x,\ x^2,\ y,\ xy,\ x^2y$ are distinct. So they are the six elements of the group: $S_{3} = \{1,\ x,\ x^2,\ y,\ xy,\ x^2y\}$. [...]

The rules [above] suffice for computation. Any product of the elements $x$ and $y$ and of their inverses can be shown to be equal to one of the products by applying the rules repeatedly. To do so, we move all occurrences of $y$ to the right side using the last rule, and we use the first two rules to keep the exponents small. For instance,

$x^{-1}y^3x^2y = x^2yx^2y = x^2(yx)xy = x^2(x^2y)xy = xyxy = x(x^2y)y = 1$.

share|improve this question
    
The reason $x^{-1}=x^2$ is that $1=x^3 = x^2x$; since the only element that when multiplied by $x$ yields $1$ is $x^{-1}$, it follows that $x{-1}=x^2$. The cancellation law comes in when showing the elements are distinct: if $x=x^2$, then cancelling we would get $x=1$, which is false; if $x^2=xy$, then cancelling $x$ we would get $x=y$, which is false. Etc. –  Arturo Magidin Feb 15 '12 at 5:18
    
Got it - thanks. –  Peter Feb 15 '12 at 5:39

1 Answer 1

up vote 2 down vote accepted

Do you understand how to multiply permutations? The rule $yx=x^2y$, for example, is just saying $$(1\ 2)(1\ 2\ 3)=(1\ 2\ 3)(1\ 2\ 3)(1\ 2)$$ and that is easy to verify if you know how to multiply permutations.

The cancellation law tells you, for example, that $x^2$ and $xy$ are distinct: if you had $x^2=xy$, then, by cancellation, you'd have $x=y$, which is manifestly false.

$x^3=1$ implies $(x)(x^2)=1$ which says $x^2$ is the inverse of $x$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.